Interruption versus continuation of trabectedin in patients with soft-tissue sarcoma (T-DIS): a randomised phase 2 trial. Issue 3 (March 2015) - Cesne, Axel Le; Blay, Jean-Yves; Domont, Julien; Tresch-Bruneel, Emmanuelle; Chevreau, Christine; Bertucci, François; Delcambre, Corinne; Saada-Bouzid, Esma; Piperno-Neumann, Sophie; Bay, Jacques-Olivier; Mir, Olivier; Ray-Coquard, Isabelle; et al.
Summary: Background: The benefit or harm of trabectedin discontinuation in patients with non-progressive soft-tissue sarcoma remains unclear. We report the final analysis of a phase 2 trial investigating the clinical benefit of continuation of trabectedin treatment until progression versus interruption of therapy after six treatment cycles in patients with advanced soft-tissue sarcoma. Methods: For this open-label, non-comparative, multicentre, phase 2 study, eligible adult patients with advanced soft-tissue sarcomas, who had previously received doxorubicin-based chemotherapy and were able to receive trabectedin, were enrolled from 14 centres of the French Sarcoma Group. Trabectedin was administered at a dose of 1·5 mg/m 2 through a central venous line as a 24-h continuous infusion every 3 weeks. After the initial six cycles of trabectedin, patients who were free from progressive disease were randomly assigned in a 1:1 ratio either to continuous treatment or therapy interruption. Randomisation was done centrally by a computer-generated system using permuted blocks of four patients, stratified by tumour grade and performance status. Patients allocated to the interruption group were allowed to restart trabectedin in case of progressive disease. The primary endpoint was progression-free survival at 6 months after randomisation, analysed by intention to treat. This study is registered withClinicalTrials.gov, numberNCT01303094 . Results: In 178 evaluable patients, 91 (51%) patients had not progressed after six cycles. Of these patients, 53 patients were randomly assigned to the two treatment groups: 27 to the continuation group and 26 to the interruption group. Overall, patients in the two groups received a similar median number of trabectedin cycles (continuation group: 11 cycles [range 6–31+] vs interruption group: 11 [range 6–23+]). After randomisation, progression-free survival at 6 months was 51·9% (95% CI 31·9–68·6) in the continuation group versus 23·1% (9·4–40·3) in the interruption group (p=0·0200). The occurrence of treatment-related grade 3 adverse events (four [16%] of 25 patients in the continuation group vs three [14%] of 21 in the interruption group) and grade 4 adverse events (one [4%] vs none) was similar in both groups. The most common grade 3 and 4 toxicities were alanine aminotransferase or aspartate aminotransferase increases (one [4%] in the interruption group vs three [14%] in the continuation group), neutropenia (two [8%] vs two [10%]), and intestinal occlusion (one [4%] vs one [5%]). Interpretation: We do not recommend trabectedin discontinuation in patients with advanced, doxorubicin-refractory soft-tissue sarcoma who have not progressed after six cycles of treatment. Funding: The French National Cancer Institute (INCa) and PharmaMar SA.